Improving Employee Performance and Discipline Through Android-Based Employee Attendance Applications: Meningkatkan Kinerja dan Disiplin Karyawan Melalui Aplikasi Absensi Karyawan Berbasis Android - Tri Sugihartono; Puad Nabil Hakiki; Maxrizal; Rendy Rian chrisna Putra (SYSTEMATICS, 2023)
Attendance is used to recap employee attendance as a whole which is used to monitor employee discipline in an agency. In monitoring employee discipline, honesty is needed at work. In this conventional system, data is found that is not organized and requires extra monitoring time to determine employee discipline in carrying out the work given, in this study the focus is on employee absenteeism. The development of Information Technology is currently very rapid, and is balanced with the need for data processing tools that can manage information in certain fields. With the development of Information Technology and the increasing need for communication and information globally, it is necessary to have a mobile-based employee attendance application that is integrated with the location of accurate coordinates. Therefore, this study discusses the application of Android-Based Employee Attendance Application to Improve Employee Performance and Discipline. This study uses data collection techniques using the questionnaire method, while the data obtained using primary data, namely quantitative data. the results of this study as many as 50 employees are more responsible for the work given and always come on time. Thus it can be concluded that by implementing an employee attendance application, employees are responsible for the work given and always come on time and always provide information if unable to attend.